Distribution of lung density after strenuous, prolonged exercise - Manier, G.; Duclos, M.; Arsac, L.; Moinard, J.; Laurent, F. (Journal of Applied Physiology, 1999)
The postexercise alteration in pulmonary gas exchange in high-aerobically trained subjects depends on both the intensity and the duration of exercise (G. Manier, J. Moinard, and H. Stoicheff. J. Appl. Physiol. 75: 2580-2585, 1993; G. Manier, J. Moinard, P. Techoueyres, N. Varene, and H. Guenard. Respir. Physiol. 83: 143-154, 1991). In a recent study that used lung computerized tomography (CT), evidence was found for accumulation of water within the lungs after exercise (C. Caillaud, O. Serre-Cousine, F. Anselme, X. Capdevilla, and C. Prefaut. J. Appl. Physiol. 79: 1226-1232, 1995). On representative slices of the lungs, mean lung density increased by 0.040 +/- 0.007 g/cm(3) (19%, P < 0.001) in athletes after a triathlon. To verify and quantify the mechanism, we determined the change in pulmonary density and mass after strenuous and prolonged exercise using another exercise protocol and methodology for CT scanning. Nine trained runners (age 30-46 yr) volunteered to participate in the study. Each subject ran for 2 h on a treadmill at a rate corresponding to 75% of maximum O(2) consumption. CT measurements were made before and immediately after the exercise test with the subject supine and holding his breath at a point close to functional residual capacity. The lungs were scanned from the apex to the diaphragm and reconstructed in 8-mm-thick slices. Attenuation values of X-rays in each part of the lung were expressed in Hounsfield units (HU), which are related to density (D): D = 1 + HU/1,000. No significant alteration in pulmonary density (0.37 +/- 0.04 vs. 0.35 +/- 0.03, not significant) was observed after the 2-h run test. Although lung volume slightly increased (change of 166 +/- 205 ml, P < 0.05), lung mass remained stable because of a change in density distribution. We failed to detect any changes in postexercise lung mass, suggesting that other mechanisms need to be considered to explain the observed alterations in pulmonary gas exchange after prolonged strenuous exercise.